Production of γ-decalactone by Yarrowia lipolytica : insights into experimental conditions and operating mode optimization - Braga, Adelaide (2015)
BACKGROUND γ-Decalactone production from ricinoleic acid biotransformation derived from the triglycerides in castor oil by Yarrowia lipolytica, has been widely described in literature in studies concerning lipidic metabolism that leads to lactones production, interactions of cells with the lipid substrate, toxicity of produced metabolites, selection of over-producing mutants and selection of environmental conditions. RESULTS In order to improve technological aspects of γ-decalactone production, oxygen transfer rate (OTR), cell density and oil concentration effects were investigated, in batch and step-wise fed-batch cultures of Yarrowia lipolytica W29. The best γ-decalactone concentration of 5.4 ± 0.5 g L-1 was obtained for batch cultures with 60 g L-1 of cells and substrate concentration. CONCLUSION The direct influence of aeration and agitation rates, thus of OTR, on production of γ-decalactone has been demonstrated. γ-Decalactone productivity of 215 ± 19 mg L-1 h-1 was obtained with 60 g L-1 of cells and castor oil concentration in batch and step-wise fed-batch cultures of Yarrowia lipolytica. The results obtained suggest that these two strategies are good alternatives for industrial production processes.